(E)-1-(2,4-Dinitrophenyl)-2-pentylidenehydrazine - Neunfeldt, P.D.; Duval, A.R.; Cunico, W.; Wardell, S.M.S.V.; Tiekink, E.R.T.; Wardell, J.L. (International Union of Crystallography, 2010)
The title compound, C(11)H(14)N(4)O(4), is essentially planar with an r.m.s. deviation for the 19 non-H atoms of 0.152 angstrom. The conformation about the C=N bond is E, and the molecule has a U-shape as the butyl group folds over towards the aromatic system. An intramolecular C-H center dot center dot center dot N interaction occurs. The crystal packing is dominated by N-H center dot center dot center dot O hydrogen bonding and C-H center dot center dot center dot O contacts, leading to twisted zigzag supra-molecular chains along the c direction. The crystal packing brings two nitro O atoms into an unusually close proximity of 2.686 (4) angstrom. While the nature of this interaction is not obvious, there are several precendents for such short nitro-nitro O center dot center dot center dot O contacts of less than 2.70 angstrom in the crystallographic literature.